The role of p300 in cardio-oncology: implications for breast and prostate cancer treatments and impact on vascular function - Kunkel, Olivia Nicolle (My University, 2024)
In men and women in the United States, prostate and breast cancer account for nearly a third of all new cancer diagnoses each year. Though the five-year survival is over 90% for both, those with metastatic disease have a five-year survival closer to 30%. For many of these individuals, treatment with radiation, chemotherapy, or a combination of several therapies is curative. However, many individuals will experience treatment failure or severe side effects that require early cessation of standard treatment, which is associated with increased recurrence and worse survival outcomes. As such, finding adjuvant treatment options that can enhance treatment efficacy and limit side effects is of critical importance. Given the evidence supporting the role of p300 in DNA damage repair, which is an important factor mediating the efficacy of radiation, we sought to understand whether p300, a histone acetyltransferase and transcriptional coactivator, or its homologue CREB binding protein (CBP), plays a role in the success of radiation therapy in humans by performing a candidate gene association study (Chapter 2). We found that there are several p300 and CBP single nucleotide polymorphisms (SNPs) associated with the odds of diagnosis of a second malignancy after radiation, suggesting that they may play a role in the efficacy of radiation therapy in humans. As a follow-up to these findings, we investigated the role of p300/CBP in the radiosensitivity of human prostate and breast cancer cells in vitro through pharmacological inhibition. Results from this work did not reveal any effect of p300/CBP inhibition on prostate or breast cancer cell survival after radiation. In chapter 3, we further investigated the role of p300/CBP in the response to doxorubicin, a first line drug for metastatic breast cancer. First, we investigated whether p300 or CBP plays a role in the success of doxorubicin by performing a candidate gene association study. We found that there are several CBP, but no p300, SNPs that decrease the odds of second malignancy after doxorubicin, suggesting that CBP may play a role in the efficacy of doxorubicin. We followed these findings with in vitro experiments to determine the role of p300/CBP inhibition on breast cancer cell survival after exposure to doxorubicin and found that p300/CBP inhibition had no effect on the efficacy of doxorubicin. We also sought to determine if p300/CBP modulates the effects of doxorubicin on the vasculature, a physiological target for development of adverse cardiotoxicity, by investigating vascular reactivity of the thoracic aorta in rats, finding that there was no effect of either p300/CBP inhibition or doxorubicin ex vivo. Finally, in chapter 4, we sought to characterize the vascular, skeletal muscle mass, and cardiac mass changes in an orthotopic model of breast cancer. We found that independent of any treatment, the breast tumor vasculature exhibits impaired ⍺-adrenergic vasoconstriction and that skeletal muscle, but not cardiac muscle, atrophy may occur, mirroring several findings that have been demonstrated in orthotopic prostate cancer models. Together, our findings suggest that there may be an association between p300/CBP and the odds of diagnosis of secondary malignancy after exposure to anti-cancer therapies. However, further investigation is needed to determine the exact role of p300/CBP on the efficacy of current first line anti-cancer therapies. We also determined that the orthotopic breast cancer model extends several findings from orthotopic models of prostate cancer, suggesting it may be useful to study interventions that rely on hemodynamic alterations.
Keywords: Prostate cancer; Breast cancer; Radiation; Doxorubicin; p300; Cardio-oncology